Alimentação adequada e saudável no campus Belém da Universidade Federal do Pará: estudo de caso das ações e programas institucionais voltados para alunos e servidores - SOUSA, Tanha Charle Santa Rosa de (Universidade Federal do Pará, 2023)
The right to food is inherent to the human being, therefore inalienable and independent of any legislation. However, the recognition of this right in norms, agreements, declarations and other instruments is important to ensure its enforceability by the holders and compliance by the State. In 2014, the Ministry of Health updated the new version of the Food Guide for the Brazilian Population, which is one of the national strategies to promote adequate and healthy food that integrates the National Food and Nutrition Policy, aiming to provide individuals and the community with dietary practices appropriate. In this context, the University Restaurant (RU) is an environment conducive to the promotion of adequate diets and the development of healthy eating habits, a precept that should be extended to all places authorized to offer food to the academic community. Thus, the research problem arises: how, at the Federal University of Pará, are actions aimed at encouraging and controlling adequate nutrition offered to students and civil servants, with the aim of developing healthy eating habits? Thus, the general objective of the work is to analyze how UFPA develops actions and programs to encourage and control an adequate and healthy food for students and employees at the Campus of Guamá in Belém, having as a parameter of analysis the national and institutional guidelines for the development of healthy eating habits. Thus, once the case was defined and the field delimited, the research carried out was of a mixed type, based on multiple case study techniques in a quantitative and qualitative approach, in which a bibliographic and documental survey was carried out. Then, a deductive diagnostic analysis of the case was carried out from the bibliographical and documental landmarks based on the interpretation of the data. In this way, the research verified how UFPA promotes programs and actions to promote adequate and healthy eating by the community of students and civil servants, having as an analysis criterion the guidelines of: WHO, the Food Guide for the Brazilian population (2014), the National Food and Nutrition Policy, the National Food and Nutrition Security System, the National Food and Nutrition Security Policy, the National Student Assistance Program and the Integrated Attention Subsystem to Server Health. The product of the master's final work is a case study with the presentation of a Diagnostic Report and a scientific article.